PENYULUHAN BERBUDIDAYA JAMUR SKALA RUMAH TANGGA UNTUK IBU-IBU DASAWISMA DUSUN TOTOGAN DESA MADUREJO, KECAMATAN PRAMBANAN, KABUPATEN SLEMAN, DIY - Pranoto, Aji; Novianta, Muhammad Andang; Parwati, Cyrilla Indri (LPPM IST AKPRIND Yogyakarta, 2021)
Household industries that are engaged in the percentage of the agribusiness sector,especially mushrooms, are still relatively small compared to those engaged in other sectors.This has become one of the factors for entrepreneurship to improve people's welfare,especially housewives. Mushroom cultivation does not require much capital and byunderstanding proper maintenance procedures will decrease the failure rate of mushroomcultivation. With an average harvest age of 2 weeks since planting, the optimal processingwill quickly generate profits. This community service aims to provide counseling aboutmushroom cultivation on a household scale, by knowing the process of mushroom cultivationusing automatic mushroom incubator, types of mushrooms that can be consumed and thebenefits of mushroom cultivation. The expected results of this activity are Dasawisma womenRT.06 Kampung Totogan, Madurejo Village, Prambanan Subdistrict, Sleman Regency, DIYcan play an active role in efforts to rise living standards and also improve communitywelfare by cultivating mushrooms using household scale automatic mushroom incubator, solater it will create a household business in the field of agribusiness.